Misalignment Effects in Laser-Induced Grating Experiments. Issue 12 (December 2016) - Kiefer, Johannes; Sahlberg, Anna-Lena; Hot, Dina; Aldén, Marcus; Li, Zhongshan
Laser-induced grating spectroscopy (LIGS) is an experimental method in which two pulsed laser beams and a continuous-wave laser beam have to be superimposed under well-defined angles to generate a coherent signal beam. In this Note, the possible effects of different forms of misalignment are examined. This includes the overlap of the pump lasers as well as the influence of the probe laser alignment on the temporal profile of the signal.